Discovery of a Recombinant Human Monoclonal Immunoglobulin G Antibody Against α-Latrotoxin From the Mediterranean Black Widow Spider (Latrodectus tredecimguttatus) - Føns, Sofie; Ledsgaard, Line; Nikolaev, Maxim V.; Vassilevski, Alexander A.; Sørensen, Christoffer V.; Chevalier, Manon K.; Fiebig, Michael; Laustsen, Andreas H. (Frontiers in Immunology, 2020)
Widow spiders are among the few spider species worldwide that can cause serious envenoming in humans. The clinical syndrome resulting from Latrodectus spp. envenoming is called latrodectism and characterized by pain (local or regional) associated with diaphoresis and nonspecific systemic effects. The syndrome is caused by α-latrotoxin, a ~130 kDa neurotoxin that induces massive neurotransmitter release. Due to this function, α-latrotoxin has played a fundamental role as a tool in the study of neuroexocytosis. Nevertheless, some questions concerning its mode of action remain unresolved today. The diagnosis of latrodectism is purely clinical, combined with the patient’s history of spider bite, as no analytical assays exist to detect widow spider venom. By utilizing antibody phage display technology, we here report the discovery of the first recombinant human monoclonal immunoglobulin G antibody (TPL0020_02_G9) that binds α-latrotoxin from the Mediterranean black widow spider (Latrodectus tredecimguttatus) and show neutralization efficacy ex vivo. Such antibody can be used as an affinity reagent for research and diagnostic purposes, providing researchers with a novel tool for more sophisticated experimentation and analysis. Moreover, it may also find therapeutic application in future.